Vitamins E, A and B2 as Possible Risk Factors for Preeclampsia – under Consideration of the PROPER Study (“Prevention of Preeclampsia by High-Dose Riboflavin Supplementation”) - Elsen, C.; Rivas-Echeverría, C.; Sahland, K.; Sánchez, R.; Molma, L.; Pahl, L.; Wallinger, R.; Volz, J.; Wacker, J.; Frühauf, J. (Geburtshilfe und Frauenheilkunde, 2012)
In the course of the prospective, randomized, double-blind trial the influence of a high-dose riboflavin substitution on the risk for preeclampsia was studied in a high-risk collective 1. The present contribution evaluates supplementary data from the already published PROPER trial. The patients were from the two study centers Mérida, Venezuela, and Moshi, Tanzania, they were randomized from the 20th week of pregnancy and received either 15 mg riboflavin daily or placebo. Clinical and laboratory checks were carried out at four-week intervals up to childbirth. Concerning the question of whether there is a relationship between the serum levels of antioxidative vitamins and the risk of developing preeclampsia, it was found that no relationship could be detected between the measured laboratory values of vitamins E, A and B2 and the total risk of developing a hypertensive disease of pregnancy. On comparisons between patients with severe preeclampsia, those with a mild form, and the general healthy population, however, significant differences in the levels of antioxidative vitamins E and A as well as the FAD level were seen. The patients from Tanzania showed on the whole significantly lower vitamin levels than those from Venezuela, possibly due to the better nutritional situation in Venezuela. Considering the results altogether, the role of antioxidative parameters in the pathophysiology of preeclampsia remains unclear. However, the collected data provide valuable hints for future preventative strategies.
Keywords: Preeclampsia; obstetrics; childbirth